Doing academic research a practical guide to research methods and analysis - Gournelos, Ted 1979-; Hammonds, Joshua R.; Wilson, Maridath A. (Routledge, 2019)
Doing Academic Research is a concise, accessible, and tightly organized overview of the research process in the humanities, social sciences, and business. Conduction effective scholarly research can seem like a frustrating, confusing, and unpleasant experience. Early researchers often have inconsistent knowledge and experience, and can become overwhelmed - reducing their ability to produce high quality work. Rather than a book about research, this is a practical guide to doing research. it guides budding researchers along the process of developing an effective workflow, where to go for help, and how to actually complete the project. The book addresses diversity in abilities, interest, discipline, and ways of knowing by focusing not just on the process of conducting any one method in detail, but also on the way in which someone might choose a research method and conduct it successfully. Finally, it emphasizes accessibility and approachability through real-world examples, key insights, tips, and tricks from active researchers. This book is a highly useful addition to both content area and research methods courses, as well as a practical guide for graduate students and independent scholars interested in publishing their research